REFLECTION AS A FACTOR OF THE ACTIVITY OF PROFESSIONAL COMPETENCE OF SOCIAL PEDAGOGUES - Indrašienė, Valdonė; Sadauskas, Justinas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The study analyses the role of reflection in the context of professional improvement as one of the assumptions for profession competence of the social pedagogues. It is noted that reflection of professional experience is important in the preparation of the specialists providing social pedagogic assistance and in the improvement of their competence to act in both defined and undefined professional situations. Applying the qualitative research it has been established that in order to improve the provision of social pedagogic assistance it is important to continuously reflect on own professional activity. The research has established that reflection is one of the factors of the competence of specialists of the social pedagogics, since reflection of individual experience allows to consider actions, practicable methods, to foresee the results and the impact on the situation, on other people and on the person.